Covid-19, Remittance Inflow, and Economic Growth Rate in Nepal - Chaudhary, Arbind (Tribhuvan University Journal, 2020)
The proliferation of COVID-19 pandemic over the globe is anomalously hurting the world’s economy. The paper aims to reveal the possible loss in economic growth rate for FY 2020 due to plausible retardation in remittance/GDP size of Nepal under COVID- 19 regime by utilizing transmission approach, trend forecast, and ordinary least square method form 2000 to 2019. The study harvests two premises: first, remittance/GDP has a positive estimate to the economic growth rate and second, if the pandemic proliferates more, and if it downsizes the remittance/ GDP size by 25% to 75%, it reduces the projected GDP growth rate (6.95) up to 6.68 to 5.3% respectively for FY 2020. However, domestic literature also supports the strong role of remittance on the micro-level. Therefore, the microeconomic impact of the virus may be more appalling than the macro-economic ground.